2009
DOI: 10.1007/s11250-008-9291-6
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro nutritive evaluation and rumen fermentation kinetics of Sesbania aculeate as affected by harvest time and cutting regimen

Abstract: The nutritive value of Sesbania aculeate harvested after 60 and 120 days of planting and subjected to two cutting regimen (15 or 30 cm length) was evaluated by determination of the crude protein (CP), crude fibre (CF), buffer soluble nitrogen (BS-N), buffer soluble non-protein nitrogen (BS-NPN) and cell wall constituents (neutral-detergent fibre; NDF, acid-detergent fibre; ADF and lignin). In vitro digestible organic matter (IVDOM), metabolizable energy (ME), microbial nitrogen (MN) and biomass (MBM) productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The CP content of even Moringa stem of different cultivars was higher than that of Napier or Guinea grass (109.0 g kg -1 DM and 91.7 g kg -1 DM, respectively; [27,28]. The CP contents of Moringa tops reported in this study are within the range of 193.0 to 264.0 g kg -1 DM, reported earlier [25,29,30,31,32,33,34,35]. The CP of Moringa tops containing leaf to stem ratio of 0.53:1 of the present study was 22.4% (Table 3).…”
Section: IVsupporting
confidence: 69%
See 1 more Smart Citation
“…The CP content of even Moringa stem of different cultivars was higher than that of Napier or Guinea grass (109.0 g kg -1 DM and 91.7 g kg -1 DM, respectively; [27,28]. The CP contents of Moringa tops reported in this study are within the range of 193.0 to 264.0 g kg -1 DM, reported earlier [25,29,30,31,32,33,34,35]. The CP of Moringa tops containing leaf to stem ratio of 0.53:1 of the present study was 22.4% (Table 3).…”
Section: IVsupporting
confidence: 69%
“…The CP of Moringa tops containing leaf to stem ratio of 0.53:1 of the present study was 22.4% (Table 3). When it was compared with other feed sources ( [32] and AlMashri [25]. However, different stem to leaf ratio of a harvest affected the level of different cell wall components in different cultivars of Moringa.…”
Section: IVmentioning
confidence: 99%
“…Significantly (p<0.01) highest and lowest gas production was recorded at 30R:70C and 100R:0C, respectively ( Table-3 ). This increase in gas production with increased concentrate proportion in the inoculum, might be due to increase in the nutrient availability from concentrate [ 19 ] or might be due to lowered cell wall and lignin content in the inoculum as reduction in roughage proportion in the inoculum, which negatively affect the microbial attachment to the feed particles [ 20 , 21 ]. Similar to our results, previous researchers [ 22 - 24 ] also observed an increase in gas volume as a proportion of roughage was replaced by concentrate in the complete ration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to gas production, IVOMD, TDOM, and ME values were increased linearly as the concentrate proportion increased from 0% to 70% ( Table-3 ). The increased values might be due to gradual reduction in hemicellulose, cellulose, and lignin content in inoculum from 100R:0C to 30R:70C which act as limiting factors to lower the digestibility at excess amount [ 20 , 21 ] or increased nutrient availability to microorganisms from increased proportion of concentrate in the ration [ 19 ]. Similarly, Polyorach et al .…”
Section: Discussionmentioning
confidence: 99%
“…Others (Reddy et al, 2016) reported that in vitro OMD and TDOM increased linearly with the increase of concentrate proportion in the diet. They attributed such increase to gradual decrease in cellulose and lignin in their diets, which act as a limiting factor to lowering digestibility (Al-Masri, 2009 andKumari et al, 2012). The increase of in-vitro OMD in rations I, II, III and IV containing 100, 80, 60 and 40% concentrate, respectively (Table 3) might be due to the increase of readily available energy and protein contents of these rations which might have improved microbial growth and fermentation (Chatterjee et al, 2006).…”
Section: In Vitro Rumen Methane Emission Characteristicsmentioning
confidence: 99%